Novel Magnetic Resonance Imaging for Assessment of Bronchial Stenosis in Lung Transplant Recipients. Issue 7 (8th May 2017) - Mahmood, K.; Ebner, L.; He, M.; Robertson, S. H.; Wang, Z.; McAdams, H. P.; Wahidi, M. M.; Shofer, S. L.; Huang, Y. T.; Driehuys, B.
Abstract : Bronchial stenosis in lung transplant recipients is a common disorder that adversely affects clinical outcomes. It is evaluated by spirometry, CT scanning, and bronchoscopy with significant limitations. We hypothesize that MRI using both ultrashort echo time (UTE) scans and hyperpolarized (HP) 129 Xe gas can offer structural and functional assessment of bronchial stenosis seen after lung transplantation. Six patients with lung transplantation–related bronchial stenosis underwent HP 129 Xe MRI and UTE MRI in the same session. Three patients subsequently underwent airway stent placement and had repeated MRI at 4‐week follow‐up. HP 129 Xe MRI depicted decreased ventilation distal to the stenotic airway. After airway stent placement, MRI showed that low‐ventilation regions had decreased (35% vs. 27.6%, p = 0.006) and normal‐ventilation regions had increased (17.9% vs. 27.6%, p = 0.04) in the stented lung. Improved gas transfer was also seen on 129 Xe MRI. There was a good correlation between UTE MRI and independent bronchoscopic airway diameter assessment (Pearson correlation coefficient = 0.92). This pilot study shows that UTE and HP 129 Xe MRI are feasible in patients with bronchial stenosis related to lung transplantation and may provide structural and functional airway assessment to guide treatment. These conclusions need to be confirmed with larger studies. Abstract : When used in lung transplantation–related bronchial stenosis, magnetic resonance imaging with ultrashort echo time and hyperpolarized xenon provides structural and functional assessment.